A person-centred care intervention provided via eHealth to reduce fatigue in patients with common mental disorders – secondary outcome analysis from a randomized controlled trial - Sara Alsén; Matilda Cederberg; Andreas Fors (Scandinavian Journal of Primary Health Care)
Background The number of people with common mental disorders (CMDs) has increased in several countries, including Sweden, during the past decade. Patients seeking care for CMDs report severe symptoms. Although person-centred care has shown several benefits, studies evaluating the effects of person-centred eHealth interventions on patients with CMDs are scarce.Objective The aim of this study was to evaluate the effects of a person-centred eHealth intervention on self-reported fatigue in patients with CMDs.Methods This study reports analysis of a secondary outcome measure from a randomised controlled trial. Patients (n = 209) on sick leave for CMDs were recruited from nine primary health care centres and allocated to either a control group (n = 107) receiving treatment as usual (TAU) or an intervention group receiving TAU with the addition of a person-centred eHealth intervention (phone support and an interactive digital platform) (n = 102). Self-reported symptoms of fatigue were assessed using the Multidimensional Fatigue Inventory Scale (MFI-20).Results The intervention group improved significantly more than the control group in global fatigue and three of five dimensions of the MFI-20 (Physical fatigue, Reduced activity, and Mental fatigue) at the 3- and 6-month follow-ups. In the General fatigue dimension, the intervention group showed significant improvement at 6 but not at 3 months, while for Reduced motivation, there was a significant difference in favour of the intervention at 3 but not at 6 months.Conclusion A person-centred eHealth intervention combining telephone support and an interactive platform holds potential for reducing symptoms of fatigue in patients on sick leave due to CMDs.Trial registration The trial was registered in ClinicalTrials.gov (Identifier NCT03404583). Date of registration: 19 January 2018. https://clinicaltrials.gov/ct2/show/NCT03404583.